Online hate via social media platforms: challenges under legislation of the European Union - Frišfelde, Zanda (Riga Graduate School of Law, 2023)
This thesis seeks to answer the following research question: do social media platforms appropriately balance the fundamental rights of the victims with the right to freedom of expression under laws regulating hate speech in the European Union? To achieve the goals of the thesis, the author uses legal dogmatic methodology and doctrinal legal research. The aim of the thesis is to develop a deeper understanding of the European Union legal framework applicable to social media platforms concerning tackling online hate speech, and victims’ perspectives in this regard. Within the scope of the thesis the author analyses the current legal environment, victims’ rights and an exercise of their rights, self-regulatory initiatives invented by social media platforms and new legislation from the European Union legislators -the Digital Service Act. In conclusion, the author argues that the applicable legislative acts demanding social media platforms to determine user-uploaded content as illegal and remove it without providing mandatory safeguards for freedom of expression, as well as the ruling on the major case regarding the freedom of expression on the internet and the obligations of the hosting service providers decided by the Court of Justice of the European Union, are balancing in favour of the complainants (victims) and against online speech. However, the Digital Service Act promises to improve the current legal framework from the freedom of expression perspective by establishing a transparency and accountability framework for online platforms into content moderation programs, practices and decisions and providing a single, uniform framework across the European Union.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Human rights law; freedom of expression; social media; online hate